A new gas–solid reaction model for voloxidation process with spallation - Ryu, Je Ir; Woo, Seung Min (Nuclear engineering and technology, 2018)
A new methodology, the crack–spallation model, has been developed to analyze gas–solid reactions dominated by crack growth inside of the solid reactant and spallation phenomena. The new model physically represents three processes of the reaction progress: (1) diffusion of gas reactant through pores; (2) growth of product particle in pores; and (3) crack and spallation of solid reactant. The validation of this method has been conducted by comparison of results obtained in an experiment for oxidation of UO2 and the shrinking core model. The reaction progress evaluated by the crack–spallation model shows better agreement with the experimental data than that evaluated by the shrinking core model. To understand the trigger point during the reaction progress, a detailed analysis has been conducted. A parametric study also has been performed to determine mass diffusivities of the gas reactant and volume increase constants of the product particles. This method can be appropriately applied to the gas–solid reaction based on the crack and spallation phenomena such as the voloxidation process.